Pengaruh Total Assets Turnover, Debt To Equity Ratio, dan Current Ratio Terhadap Return On Assets - Galuh Chandra Kirana; Munari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The aim of this research was to determine the influence of Total Asset Turnover, Debt to Equity Ratio, and Current Ratio on Return On Assets in food and beverage sector manufacturing companies listed on the IDX for the 2020-2022 period. This research was conducted using a quantitative approach with secondary data, namely financial reports of food and beverage manufacturing companies listed on the IDX for the 2020-2022 period. The sample in this study was 19 companies and was analyzed using multiple linear regression analysis. The results of the research show that total asset turnover partially has a positive and significant effect on return on assets, debt to equity ratio partially has a negative and significant effect on return on assets, current ratio partially has a negative and insignificant effect on return on assets, and together – Total asset turnover, debt to equity ratio, and current ratio simultaneously influence return on assets in food and beverage sector manufacturing companies on the IDX for the 2020-2022 period.